FROM FIQH TO POLICY INSTRUMENT: THE LEGAL TRANSFORMATION OF ISLAMIC ECONOMIC PRINCIPLES - Omar Al Fahim; Fatima Al Mazrouei; Sarah Williams (Sharia Oikonomia Law Journal, 2026)
Islamic economic principles have undergone significant transformation as they move from classical fiqh-based reasoning into contemporary policy instruments within modern governance systems. This shift reflects increasing institutionalization, regulatory demands, and integration into global financial frameworks, raising questions about how normative legal doctrines are reinterpreted and operationalized. This study aims to examine the nature of this legal transformation and to analyze how jurisprudential principles are translated into enforceable policy frameworks across different institutional contexts. A qualitative normative–juridical research design is employed through systematic analysis of 94 legal documents, including classical texts, fatwas, and regulatory standards from multiple jurisdictions. Analytical matrices and thematic coding are used to identify patterns of doctrinal adaptation, institutional mediation, and policy codification. The findings reveal that legal transformation is a multi-layered process involving doctrinal preservation, interpretive mediation, and regulatory abstraction, often resulting in reduced normative depth as principles become standardized. Institutional governance plays a critical role in shaping the extent to which ethical foundations are retained or simplified. The study concludes that the transformation from fiqh to policy instrument requires integrative governance models that balance interpretive richness with regulatory functionality, ensuring alignment between normative objectives and contemporary economic realities.